An Unusual Transorbital Penetrating Injury by House-key (lock): A Case Report with a Small Review of Literature - Sarkar, Santanu (J Clin Diagn Res, 2015)
Penetrating injuries of the brain are quite uncommon, comprising approximately 0.4% of all head injuries. In our case, a four-year-old boy who fell forward on a house-key (lock) accidentally while playing with some other children sustained a left sided penetrating transorbital brain injury. After hospital admission, the patient had a Glasgow Coma Scale (GCS) score of 15/15, no visual loss but restriction of upward gaze (left eye) and profuse bleeding from the wound site. Firstly, the metallic key was removed in emergency operation theatre and haemostasis secured. Next day we did a combined surgical approach with neurosurgeons, Eye-surgeons and general surgeons after having CT scan report. We report this case because penetrating head injury is rare and transorbital penetrating head injury is even rarer and a predicament in emergency surgical practice with controversial management.